Rediscovery of the rare Mediterranean marine cave stenopodid shrimp Odontozona addaia Pretus, 1990, 30 years after its original description (Crustacea: Decapoda: Stenopodidea) - Chevaldonné, Pierre; Pretus, Joan Ll. (Zootaxa, 2021)
Thirty years after its first finding and description, the marine cave stenopodid shrimp Odontozona addaia is here reported for the second time. The new localities, particular marine caves of southern France, are more than 300 km apart from the type locality in the Balearic Islands. First live in situ photographs are provided, and the morphological intraspecific variability is detailed by comparing the new specimens to the types. DNA sequences were also obtained for comparison with other Odontozona species. Based on both morphology and molecular analysis, closest relatives of O. addaia appear to be the western Atlantic Odontozona meloi and the eastern Mediterranean Odontozona minoica, although their detailed relationships remain unresolved.